Antecedentes e consequentes ?? sobrecarga de informa????o em vendedores de lojas f??sicas de varejo - Andrade, Enos Neves Coelho de (2014)
This project reproduces the research of Hunter and Goebel (2008) on Salesperson s Information Overload, which is a state of a salesperson suffering the effects of information overload. This phenomenon was conceptually developed and related to consequential variables, including Job Satisfaction and Sales Performance, and antecedents variables, such as Polychronic Attitude, Need for Cognition and Role Overload. The innovation aspect of this study was the use of a different country and a different salesperson profile in comparison to the original research. The country focused was Brazil, and the salesperson was from a retail construction material physical store. Another innovation was the application of a different analysis approach, which was the Stuctural Equation Model, combined with the Partial Least Squares (PLS) method. The results demonstrated a significant positive correlation between Role Overload and Need for Cognition. The study also pointed out that a salesperson with more Need for Cognition usually suffers less the effects of Information Overload. With regards to the consequences, the results indicated that Information Overload reduces both Job Satisfaction and Sales Performance. Suggestions for future researches and limitations are reported at the end of this project.